If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + -3) = 3x + 15 Reorder the terms: 7(-3 + x) = 3x + 15 (-3 * 7 + x * 7) = 3x + 15 (-21 + 7x) = 3x + 15 Reorder the terms: -21 + 7x = 15 + 3x Solving -21 + 7x = 15 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -21 + 7x + -3x = 15 + 3x + -3x Combine like terms: 7x + -3x = 4x -21 + 4x = 15 + 3x + -3x Combine like terms: 3x + -3x = 0 -21 + 4x = 15 + 0 -21 + 4x = 15 Add '21' to each side of the equation. -21 + 21 + 4x = 15 + 21 Combine like terms: -21 + 21 = 0 0 + 4x = 15 + 21 4x = 15 + 21 Combine like terms: 15 + 21 = 36 4x = 36 Divide each side by '4'. x = 9 Simplifying x = 9
| 4(2x-3/4)=53 | | 455=O | | -3/4=c+7/10 | | 444/100-1/12=x | | 95=O | | x/2-6=-4 | | 4+m/5=8 | | 13(ab)= | | 2/3y-1=7 | | 9x+12=8x-10 | | 14x^2+4x= | | x-3+12=134 | | 3g+4n=18 | | v/8+2 | | 2x+4.1=x+1.1 | | n=9200ln(5(3)+3) | | 5/4x5/3(2+10) | | 2n+8=8 | | 8(x-3)=4x+-8 | | 4x^2-6x-56=3x-16 | | 4/5y-9=-1 | | 4a+3=56 | | 2/2/3x8 | | 15+h=-15 | | 4x-7(x-2)= | | 8x+11/9=-5 | | log(2x-8)-log(6x)=2 | | x^3+10x^2+9x=0 | | 22/3x8 | | 7+9n=79 | | 20x^3+60x^2+25x=0 | | 3x^2+7+8=6 |